Characterization of lactoferrin in gingival crevicular fluid of chronic periodontitis patient - Sisca Meida Wati; Istiati Istiati; Pratiwi Soesilawati (Dental Journal (Majalah Kedokteran Gigi), 2014)
Background: Human periodontal diseases are inflammatory disorders as the result of complex interactions between periodontopathogens and the host’s immune response. Periodontitis results in tooth loss and can even lead to systemic diseases if not treated. Gingival crevicular fluid (GCF) reflects the condition of the gingiva and contains proteins transuded from serum or cells at inflamated sites. Polymorphonuclear leukocyte (PMNs) infiltration can be seen in each stage of periodontitis. Lactoferrin is one of the PMN specific granules and could be a useful marker of PMN activity. Purpose: The aim of this study was to determine the band intensity of lactoferrin used as periodontitis biomarker. Methods: Gingival crevicular fluid (GCF) samples were collected using paper point no.30 from 40 subjects, 30 periodontitis patients that devide according to the severity (10 mild periodontitis, 10 moderate periodontitis, and 10 severe periodontitis) and 10 healthy controls, ranging in ages from 20 to 35 years. GCF lactoferrin was analyzed by Western blot and measured the band intensity by quantity one software (bio-rad). Results: The periodontitis sites exhibited significantly greater band intensity of lactoferrin than healthy sites. The band intensity of lactoferrin was positively correlated with the severity of periodontitis (α = 0.05). Conclusion: The study showed that the intensity of the lactoferrin protein bands could be used as biomarkers of periodontitis.Latar belakang: Penyakit periodontal adalah gangguan inflamasi yang merupakan hasil dari interaksi yang kompleks antara periodontopathogens dan respon imun host. Periodontitis mengakibatkan hilangnya gigi dan bahkan dapat menyebabkan penyakit sistemik jika tidak diobati. Cairan sulkus gingiva (GCF) mencerminkan kondisi gingiva dan mengandung protein yang tertransudasi dari serum atau sel pada lokasi radang. Infiltrasi polymorphonuclear leukosit (PMN) dapat dilihat pada setiap tahap periodontitis. Laktoferin adalah salah satu granula spesifik PMN dan bisa menjadi indicator aktivitas PMN. Tujuan: Tujuan penelitian ini adalah untuk meneliti intensitas band laktoferin dapat sebagai biomarker periodontitis. Metode: Cairan sulkus gingiva (GCF) dari tiap sampel dikumpulkan menggunakan paper pint no. 30 dari 40 subjek, 30 pasien dengan periodontitis yang dibagi sesuai dengan tingkat keparahan (10 periodontitis ringan, 10 periodontitis moderat, dan 10 periodontitis parah) dan 10 kontrol, mulai usia 20-35 tahun. GCF lactoferrin dianalisis dengan Western blot dan diukur intensitas bandnya dengan quantity one software (bio-rad). Hasil: Pada jaringan yang mengalami periodontitis menunjukkan intensitas band yang secara signifikan lebih besar dari laktoferin daripada periodontal yang sehat. Intensitas band laktoferin berkorelasi positif dengan tingkat keparahan periodontitis (α = 0,05) Simpulan: Hasil penelitian ini menyimpulkan bahwa intensitas band protein laktoferin dapat digunakan sebagai biomarker periodontitis.